Fruit characterization of 36 cape gooseberry hybrids for identification of potential industrial or fresh consumption uses - Lagos-Burbano, Tulio César; Mejía-España, Diego Fernando; Arango-Bedoya, Oscar; Villaquirán-Samboni, Zulma Yizeth; Lagos-Santander, Liz Katherine; Duarte-Alvarado, David Esteban (Sociedad Colombiana de Ciencias Hortícolas-SCCH and Universidad Pedagógica y Tecnológica de Colombia-UPTC, 2021)
The cape gooseberry is the second most exported fruit in Colombia. There are, however, little information available on genetic improvement processes and limited research on the fruit components. The objective of this study was to characterize the fruits of 36 hybrids, obtained from double haploid cape gooseberry lines from the Tibaitatá Research Center of the Colombian Corporation for Agricultural Research. Hybrids with potential uses in transformation processes or for fresh consumption were identified using Hierarchical Cluster (HC) and Principal Component Analysis (PCA) with 20 physical, physicochemical, compositional, and physiological fruit descriptors, obtained from four trials in the Andean region of southern Colombia. According to the PCA, three components represented 73.6% of the total variability: postharvest (37.5%), sensory and nutritional quality (21.3%) and cracking percentage (14.8%). Six conglomerates were identified. Groups two, four, and six had aptitude for fresh consumption because of the size of the berry, high vitamin C content, maturity index and low cracking levels. Group one showed aptitude for processing and fresh consumption. Groups three and five registered a high seed content, low maturity rates, and a high cracking percentage.